PHYSICOCHEMICAL INVESTIGATION OF SOME GEOTHERMAL WATERS FROM SĂLAJ COUNTY, ROMANIA - AVRAM, Simona Elena; MANDIUC, Cristian; PETEAN, Ioan; TUDORAN, Lucian Barbu; BORODI, Gheorghe (Studia Universitatis Babeș-Bolyai Chemia, 2025)
Geothermal waters solve minerals from the geological layers due to their increased temperature. These minerals affect water hardness and salinity. Therefore, thermal water samples were collected from spa pools springs in Sălaj County, Romania: Broscărie (Șimleul Silvaniei), Jibou and Boghis. The physicochemical measurement reveals that Jibou water has a higher electrical conductivity of 10580 µSi/cm, caused by the higher value of total dissolved solids (TDS) of 5264 mg/l. It is followed by the water collected from Broscărie, with an electrical conductivity of 1949 µSi/cm related to TDS of 1023 mg/l. The weaker mineralization was found in Boghis water, around 619 mg/l, corresponding to an electrical conductivity of 1200 µSi/cm. Water hardness is related to the amount of CaCO3. Boghis water is the hardest, containing 356 mg/l, followed by the samples collected from Broscărie, with 178 mg/l. The water collected from Jibou is the softest of all samples, with a CaCO3 amount of about 106.8 mg/l. The mineral distribution was assessed by mineralogical optical microscopy (MOM) and X ray diffraction (XRD). The results show that NaCl crystallized as halite is responsible for the samples’ salinity, while aragonite, magnesian calcite and calcite are the minerals which cause the water hardness. Hard thermal water containing Ca and Mg are effective for rheumatoid symptoms amelioration, while salted water is optimal for skin care.